Postglacial flooding and vegetation history on the Ob River terrace, central Western Siberia based on the palaeoecological record from Lake Svetlenkoye. (May 2020) - Amon, Leeli; Blaus, Ansis; Alliksaar, Tiiu; Heinsalu, Atko; Lapshina, Elena; Liiv, Merlin; Reitalu, Triin; Vassiljev, Jüri; Veski, Siim
The hemispheric-scale climatic fluctuations during the Holocene have probably influenced the large Siberian rivers. However, detailed studies of the West Siberian Plain postglacial environmental change are scarce and the records of millennial-scale palaeohydrology are nearly absent. This paper presents the Holocene palaeoecological reconstruction based on the sedimentary record of Lake Svetlenkoye, located near the confluence of major Siberian rivers Ob and Irtysh. Postglacial history of flooding, dynamics of regional and local vegetation, sedimentation regime, geochemical changes and lake water pH were reconstructed based on multi-proxy studies. We used palaeobotanical (plant macrofossils, pollen, diatoms), geochemical (organic matter, total organic carbon and nitrogen content, carbon/nitrogen ratio) and chronological ( 14 C dates, spheroidal fly-ash particle counts) methods. The studied sediment section started to accumulate 11, 400 cal. yr BP. The initial shallow water body was flooded by Ob River waters 8100–8000 cal. yr BP as confirmed by a remarkable increase in the sedimentation rate and the accumulation rate of the aquatic vegetation proxies. The period of flooding coincides with the high humidity periods reconstructed from regional palaeobotanical records. About 6800–6700 cal. yr BP, the study site became isolated from the Ob River floodplain and remained a small lake until present. The diatom-based lake water pH estimates suggest fluctuations in the pH values during the Holocene, the recent decrease since 1960s being the most notable. The vegetation record revealed constant postglacial presence of tree taxa – Betula, Pinus and Picea – although in different pollen ratios and accumulation rates through time. The paludification of the surroundings occurred since ca. 8500 cal. yr BP.